(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
This article provides information about the distribution areas and natural reserves of raw materials of harmala vulgaris (Peganum harmala L.) in certain areas of Batken and Osh regions. We have noted natural thickets of harmala vulgaris on ten different plant communities on a total area of 92.8 hectares. The operational reserve is 40.37 tons, the volume of possible annual harvesting, taking into account the resumption, was 10.09 tons.